Development Of TEG Peltier Device For Heat Harvesting From 1.5 HP Split Unit Air Conditioning System - Muhamad Damanhuri, Amir Abdullah; Abdullah, Muhammad Ilman Hakimi Chua; Lubis, Abdul Munir Hidayat Shah; Zakaria, Muhammad Zulfattah; Hussin, Mohamed Saiful Firdaus; Kasno, Mohammad `Afif (Research India Publications, 2018)
In today’s world, recycling energy would be alternative in achieving green environment. Air conditioning shows the biggest energy consumption worldwide. Commonly air conditioning used to maintain indoor temperature. In Malaysia, split unit air conditioning system are famous for small area application. However, the heat release by condensing unit are wasted to the environment. Therefore, one peltier device using thermoelectric generator (TEG) module were develop in this experiment. The aim of this paper are to present the development of peltier device to harvest heat from condensing unit, hence convert it to electricity. The peltier device were sandwich among copper plate sizing 120mm x 60mm x 2mm. The copper plate were brazed at the discharge pipe of compressor and the other side of copper plate were attach to the heat sink where flow through by condensing water from evaporator. Six peltier were arrange respectively between copper plates. 3 case were monitor depended on the ΔT of cooling coil and condenser temperature. The maximum ΔT were observed at case 1, and simultaneously monitored voltage output for each peltier. The maximum 1.61V were collected from the split unit air conditioner after 30 minutes of operation with around 9-10 °C of ΔT. The application of TEG to harvest heat and turn into electricity shows the promising alternative for heat recovery. The current generated may useful for small scale used of electricity for household usage.